2005
DOI: 10.1073/pnas.0502716102
|View full text |Cite
|
Sign up to set email alerts
|

The candidate tumor suppressor ING4 represses activation of the hypoxia inducible factor (HIF)

Abstract: prolyl hydroxylase ͉ inhibitor of growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
139
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(151 citation statements)
references
References 34 publications
(38 reference statements)
11
139
1
Order By: Relevance
“…Interestingly, it has been shown that tumors lacking ING4 showed increased vascularization compared with ING4 expressing tumors [118]. Moreover, ING4 down-regulated angiogenesis related molecules including IL-8 and HIF-1α [117,119]. In line with these observations it has been shown that ING4 nuclear level is reduced in myeloma cells as compared to normal plasma cells, and that ING4 regulates IL-8 and OPN production by myeloma cells both in normoxia and hypoxia [95].…”
Section: Genes Involved In the Regulation Of The Pro-angiogenic Profimentioning
confidence: 75%
“…Interestingly, it has been shown that tumors lacking ING4 showed increased vascularization compared with ING4 expressing tumors [118]. Moreover, ING4 down-regulated angiogenesis related molecules including IL-8 and HIF-1α [117,119]. In line with these observations it has been shown that ING4 nuclear level is reduced in myeloma cells as compared to normal plasma cells, and that ING4 regulates IL-8 and OPN production by myeloma cells both in normoxia and hypoxia [95].…”
Section: Genes Involved In the Regulation Of The Pro-angiogenic Profimentioning
confidence: 75%
“…It is well known that ING4 is a tumor suppressor for it intervenes the activity of hypoxia inducible factor (HIF) which has an important positive role in angiogenesis and tumorigenesis. HIF promote tumor angiogenesis by inducing VEGF and other factors (Ozer et al, 2005;Colla et al, 2007). Thus, the up-regulation of VEGF by miR-150 may be mediated by ING4 (Brahimi-Horn and Pouyssegur, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The NLS1 domain is responsible for ING4 nuclear localization and interaction with p53 Zhang et al, 2005). The PHD domain, a zinc finger motif present in many nuclear proteins (Bienz, 2006), is involved in interaction with HPH-2 (Ozer et al, 2005) and H3K4me2/3 (Pena et al, 2006;Shi et al, 2006), thus linking ING4 to regulation of gene expression. A deletion mutant lacking the C-terminal 40 amino acids, including the PHD domain, is unable to interact with p65, thus abrogating the inhibitory effect of ING4 on NF-kB activity (Garkavtsev et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Our data are in keeping with previous study showing that the deletion of the last 40 amino acids abrogates the effect of ING4 on NF-kB activa tion. Interestingly, the region lacking in ING4-DEx6A contains the PHD domain, involved in the binding to HPH-2, and H3K4me2/3 (Ozer et al, 2005;Pena et al, 2006;Shi et al, 2006). Thus, alternative splicing producing ING4-DEx6 variants could impair some important functions of ING4 and modulate its contribution to specific pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation